Should de Winter T-Wave Electrocardiography Pattern Be Treated as ST-Segment Elevation Myocardial Infarction Equivalent with Consequent Reperfusion? A Dilemmatic Experience in Rural Area of Indonesia - Raymond Pranata; Ian Huang; Vito Damay (Case Reports in Cardiology)
Background. Although de Winter T-wave electrocardiography pattern is rare, it signifies proximal left anterior descending artery occlusion and is often unrecognized by physicians. The aim of this case report was to highlight the dilemma in the management of a patient with de Winter T-wave pattern in the hospital without interventional cardiology facility. Case Presentation. A 65-year-old male presented with typical chest pain since 2 hours before admission, and ECG showed sinus rhythm of 57 bpm and >1 mm upsloping ST depression with symmetric tall T in lead V2-3 characteristic of de Winter T-wave ECG pattern. He was given dual antiplatelet therapy, nitrate, statin, and anticoagulant. He refused referral to interventional cardiology available hospital. 3 hours after admission, the electrocardiography transformed into Q-waves consistent with final stages of acute STEMI and ST-segment elevation that barely meets the threshold in the guideline, and thrombolytic was administered and successful. There is a suggestion that de Winter T-wave electrocardiography should be treated as ST-segment myocardial infarction equivalent and should undergo coronary angiography; however, not every hospital has the luxury of interventional cardiology facility. The other modality for reperfusion is thrombolysis; however, without a clear guideline and scarcity of study, we prefer to resort to conservative treatment. “Fortunately,” transformation into ST-segment elevation helps us to determine the course of action which is reperfusion using thrombolytic. Conclusions. de Winter T-wave ECG pattern is not mentioned in any guidelines regarding acute coronary syndromes, and there are no clear recommendations. Physicians in rural area without interventional cardiology facility face a dilemma with the lack of evidence-based guideline. Fibrinolytic may be appropriate in those without contraindications with strong chest pain consistent with acute coronary occlusion, less than 3 hours of symptoms, and convincing de Winter T-wave ECG pattern for a rural non-PCI hospital far away from PCI capable hospital.